THE EFFECT OF ROSE AROMATHERAPY (ROSA CENTIFOLIA) ON SLEEP DURATION FOR INFANTS AGED 0-28 DAYS AT PONCOWATI PUBLIC HEALTH CENTER LAMPUNG TENGAH IN 2022 - Widiastuti, Valentina Dewi; Latifah, Neneng Siti; Samino, Samino; Yuviska, Ike Ate (JKM (Jurnal Kebidanan Malahayati), 2024)
ABSTRACT Approximately 75% of growth hormone in children is excreted during sleep. In Indonesia, quite a lot of babies have sleep problems, which is around 44.2% of babies experience sleep disorders such as frequently waking up at night, but more than 72% of parents consider sleep disturbances in infants not a problem or only consider it a small problem (Sekartini , 2012; Chandraini, 2021).Based on presurvey data by looking at data on baby sleep duration problems, which was carried out in 2 Puskesmas Kabupaten Lampung Tengah, namely at UPTD Puskesmas Bandar Jaya and UPTD Puskesmas Poncowati, it was found that 12 infants aged 0-28 days had problems sleeping at UPTD Puskesmas Bandar Jaya, while in In Poncowati Health Center, 20 babies aged 0-28 days had problems fulfilling the baby's sleep time, which was marked by fussy babies and crying, babies couldn't sleep if they weren't carried by their mothers.This study was to determine the effect of giving rose aromatherapy on the sleep duration of infants aged 0-28 days at Poncowati Health Center in Lampung Tengah in 2022.The research method was qualitative with questionnaire research instruments, thenumber of  samples were 36 respondents (infants aged 0-28 days) taken by  purposive sampling technique, data analysis using t test with a two group pretest posttest approach with control group design.Result of the study with an increase in the average quality of baby sleep after beinggiven rose aromatherapy (Rosa Centifolia) at the Poncowati Health Center, Lampung Tengah in 2022 was 33.33% higher than the average increase in infant sleep quality in the control group of 29.17%. From the t-test, the p value of 0.001 ˂ α (0.05) means that H0 is rejected and Ha  is accepted, which means that there is an influence between the two variables.The conclusion is that there is an effect of giving rose aromatherapy on the sleepduration of infants aged 0-28 days. Therefore, it is suggested that this research can be an alternative to get good sleep quality for infants aged 0-28 days. Keywords          : Infant, Rose Aromatherapy, Sleep Duration. Bibliography     : (35) 2015-2021